Electronic Word of Mouth (eWOM): Menguji Pengaruh Pengalaman Positif, Persepsi Kualitas dan Kepercayaan. Studi Kasus: Restoran di Labuhanbatu - Yudi Prayoga; Muhammad Yasir Arafat Pohan (Universitas Batanghari, 2022)
Compared to traditional methods, the Internet as a means of communication offers several advantages such as constant availability of information, efficient transfer of information and interactivity. In the context of the culinary business, the contribution of customers who want to spread positive information about restaurants is certainly very large. According to the literature, it was also conveyed that consumers believed in previous consumer experiences more than the advertisements delivered by the company. This study wants to examine the role of positive experience variables, perceived quality and trust in the eWOM behavior of restaurant customers in Labuhanbatu. The study used a quantitative approach using a questionnaire as a data collection tool. Questionnaires were distributed via google form to respondents. Respondents in this study were restaurant customers in Labuhanbatu who had carried out eWOM activities to the people around them. This study uses the SEM analysis method with the help of SMART PLS 3 software. The results of this study indicate that all predictive variables analyzed have a positive and significant influence on positive eWOM behavior in the context of a restaurant in Labuhanbatu.